2000
DOI: 10.1093/oxfordjournals.bja.a013412
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of the abdominal wall with local anaesthetic after total abdominal hysterectomy has no opioid-sparing effect

Abstract: We have measured the effect of infiltration of the deep and superficial layers of the abdominal wound on morphine consumption and pain for 48 h after operation, in 40 patients undergoing total abdominal hysterectomy, in a double-blind randomized study. Patients received wound infiltration with 0.9% normal saline 40 ml or 40 ml of 0.25% bupivacaine with epinephrine 1:200,000. There were no significant differences between groups in morphine consumption, linear analogue scores for pain at rest or on movement, nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 1 publication
3
29
0
Order By: Relevance
“…This study showed an elevated VAS score in group C above 30 mm until 8 h, which means there was significant postoperative pain even for LA. Various attempts have been made to reduce the postoperative pain of laparoscopic surgery, including intraperitoneal instillation [19], preincisional infiltration [20], intraperitoneal nebulization [21], epidural administration, and continuous intravenous infusion of local anesthetics [16]. Many clinicians have demonstrated that intraperitoneal instillation of local anesthetic reduces postoperative pain and the need for analgesic medications [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed an elevated VAS score in group C above 30 mm until 8 h, which means there was significant postoperative pain even for LA. Various attempts have been made to reduce the postoperative pain of laparoscopic surgery, including intraperitoneal instillation [19], preincisional infiltration [20], intraperitoneal nebulization [21], epidural administration, and continuous intravenous infusion of local anesthetics [16]. Many clinicians have demonstrated that intraperitoneal instillation of local anesthetic reduces postoperative pain and the need for analgesic medications [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators also examined its efficacy in laparoscopic surgery with promising results [5][6][7][8][9][10]. With laparotomy, however, the effect of PLA was not observed [13,17]. Investigators have suggested that the effects of PLA vary according to the type of surgery, perhaps due to the visceroperitoneal nociception which is not affected by peripheral incisional anesthetic injection [12].…”
Section: Discussionmentioning
confidence: 99%
“…Initial animal studies demonstrated that using anesthetic to block nerve fibers before trauma prevents hyperexcitability in the dorsal horn of the spinal cord, which is believed to be an important mechanism of central sensitization [1]. Existing literature, however, has noted conflicting results when this theory is applied clinically to postoperative pain management [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Some authors have suggested that the effects of preemptive analgesia may vary according to the type of surgery [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies related with abdominal hysterectomy demonstrated that local anesthetic wound infiltration does not decrease postoperative opioid requirements or improve patient comfort. 24,25 Local anesthetic wound infiltration may reduce post-thyroidectomy pain. Gozal et al 26 reported that bupivacaine infiltration in thyroid surgery markedly reduced opioid requirements.…”
Section: Discussionmentioning
confidence: 99%